A confession and other religious writings - Tolstoy, Leo, graf, 1828-1910.; Kentish, Jane (New York : Penguin Books, 1987)
A selection of religious writings by nineteenth-century Russian writer Leo Tolstoy, including the title selection that documents his 1879 spiritual crisis during which he decided he had accomplished nothing of lasting value in his lifetime; accompanied by an introduction and explanatory notes.
A Confession -- What is religion and of what does its essence consist? -- Religion and morality -- The law of love and the law of violence.
Translated from the Russian.
Includes bibliographical references (p. [231]-238).
Adult
Keywords: Tolstoy, Leo, -- graf, -- 1828-1910.; Tolstoy, Leo, -- graf, -- 1828-1910.; Christian life; Faith; Christian life; Faith